2006
DOI: 10.1152/ajprenal.00370.2005
|View full text |Cite
|
Sign up to set email alerts
|

Urine protein markers distinguish stone-forming from non-stone-forming relatives of calcium stone formers

Abstract: We have investigated urine protein inhibitors of calcium oxalate crystallization to determine whether variations in these proteins are associated with kidney stone disease and whether protein measurements improve the identification of stone formers compared with conventional risk factors (RF). Using Western blotting, we studied variations in the electrophoretic mobility patterns and relative abundances of crystallization-inhibitory proteins in urine from 50 stone-forming (SF) and 50 non-stone-forming (NS) firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 49 publications
1
14
0
4
Order By: Relevance
“…Such a functional redundancy is highly desirable for the kidneys to remain in a crystal-free environment to perform vital functions, and could therefore be a result of evolutionary pressure. Given that urine contains other putative macromolecule inhibitors, such as bikunin, prothromin fragment 1, inter-alpha trypsin (3,7,22,24), this type of redundancy may not be limited to OPN and THP, but may be applicable to other macromolecules. It will be of considerable interest to determine how other molecules respond to the loss of OPN and/or THP under normal and hyperoxaluric conditions, and whether loss of additional molecules could lead to more frequent and severe renal calcinosis and stones.…”
Section: Discussionmentioning
confidence: 99%
“…Such a functional redundancy is highly desirable for the kidneys to remain in a crystal-free environment to perform vital functions, and could therefore be a result of evolutionary pressure. Given that urine contains other putative macromolecule inhibitors, such as bikunin, prothromin fragment 1, inter-alpha trypsin (3,7,22,24), this type of redundancy may not be limited to OPN and THP, but may be applicable to other macromolecules. It will be of considerable interest to determine how other molecules respond to the loss of OPN and/or THP under normal and hyperoxaluric conditions, and whether loss of additional molecules could lead to more frequent and severe renal calcinosis and stones.…”
Section: Discussionmentioning
confidence: 99%
“…This protein can bind with calcium and is a tumor marker for endometrial cancer (25). Moreover, Bergsland et al (26) used Western blotting to investigate urine inhibitors from patients with stones and patients without stones and found that calgranulin B was different between these two groups. They concluded that changes in form or amount of calgranulin B may be associated with stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in the isoforms and abundance of several urine proteins, including calgranulin B, inter-␣-trypsin inhibitor, prothrombin fragment 1, and CD59, were known to be associated with stone formation (26). There have been no previous reports on their association with diabetes or other renal diseases.…”
Section: Downregulated Urinary Proteins In Diabetic Nephropathymentioning
confidence: 99%